PRINCIPLES OF INTERCULTURAL COMMUNICATION IN TEACHING LITERARY TRANSLATION (American Journal of Interdisciplinary Research and Development, 2023)
The article deals with the need to take into account the peculiarities of the process of intercultural communication while teaching literary translation as principles and develop the methodology of teaching literary translation, aimed at the cultural and linguistic identity.